PELATIHAN MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN HARIAN DALAM MENINGKATKAN KINERJA GURU NONFORMAL DI ‎KORWIL BIDANG PENDIDIKAN KECAMATAN KOKOP KABUPATEN BANGKALAN - Sayadi Sayadi (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2021)
The Daily Learning Implementation Plan describes the procedures and organization of learning activities that will be carried out to achieve a basic competency that has been defined in the content standards and described in the Daily Activity Plan. This research is a School Action Research which aims to improve teacher performance in preparing the Daily Learning Implementation Plan. The results of this study indicate that in the pre-cycle implementation, the participants were only able to get an average score of 64 to 72 for each individual, this means that in the Kokop sub-district, the participants have not been able to prepare the Daily Learning Implementation Plan properly. While in the first cycle it was found that the teacher's performance began to increase, this can be seen from the results of the implementation of the first cycle, the participants were able to get an average score of 70 to 80 for each individual, meaning that they had not been able to make the Daily Learning Implementation Plan well and did not meet the criteria set out in the first cycle. expected, therefore the training was continued in the next cycle. Based on the results of the implementation of the second cycle, the participants were able to get an average score of 80 to 90 for each individual. From the results of the second cycle, the objectives of the training were achieved, therefore the cycle was stopped.